2020
DOI: 10.1016/j.chaos.2020.110215
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning models for forecasting and analyzing the implications of COVID-19 spread on some commodities markets volatilities

Abstract: Over the past few years, the application of deep learning models to finance has received much attention from investors and researchers. Our work continues this trend, presenting an application of a Deep learning model, long-term short-term memory (LSTM), for the forecasting of commodity prices. The obtained results predict with great accuracy the prices of commodities including crude oil price (98.2 price(88.2 on the variability of the commodity prices. This involved checking at the correlation and the causali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…The commodity market can be characterised by large price changes. It reacts strongly to unexpected events and involves many players who try to anticipate each other's actions, particularly in times of high uncertainty [9]. Bakas and Triantafyllou [10] found that uncertainty effects are lower in agricultural commodities than energy commodities.…”
Section: Introductionmentioning
confidence: 99%
“…The commodity market can be characterised by large price changes. It reacts strongly to unexpected events and involves many players who try to anticipate each other's actions, particularly in times of high uncertainty [9]. Bakas and Triantafyllou [10] found that uncertainty effects are lower in agricultural commodities than energy commodities.…”
Section: Introductionmentioning
confidence: 99%
“…The rami cations of the pandemic on different economic sectors were catastrophic, the isolation and distancing regulations implemented paved the way towards an economic collapse (2). This economic recession affecting most countries has been anticipated by the World Bank (3). Such restrictions involved shutting down the frontiers, and limiting the number of ights unless necessary (4).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to collect more data and build a wide data set with linked CT and clinical information to allow additional diagnostic analysis. Sadefo Kamdem et al ( 2020 ) Boursorama database; COVID-19 dataset time series . Daily prices for 4 trading commodities; confirmed cases and total deaths in 2 countries before Apr 24, 2020 ARIMA-WBF model and LSTM model ACC: 92.13% - 97.45% Forecasting commodity prices and examining the effect of coronavirus on commodity price fluctuations.…”
Section: The Pandemic Dynamics: a Conceptual Overviewmentioning
confidence: 99%
“…The forced closure of commercial activities and the extended isolation have generated economic and social issues, drawing institutions’ attention to financial support plans concerning the former problems and community-related prevention strategies about the latter. In this context, AI strategies can prove valuable in optimizing resources and designing tools for efficient analysis: predicting the temporal evolution of different market segments (Sadefo Kamdem et al 2020 ; Polyzos et al 2020 ; Ou et al 2020 ) can result in more efficient strategies for the redistribution of funds. In contrast, the predictive analysis of mental health disorders due to high distress during the COVID-19 pandemic (Ćosić et al 2020 ), for example, can lead to the establishment of social services infrastructures where they are most needed.…”
Section: The Pandemic Dynamics: a Conceptual Overviewmentioning
confidence: 99%